Exploitation of Ultrasonic Waves to Develop and Model a Sustainable Process for Washing Denim Fabrics - Manel Ben Ticha; Nizar Meksi (Journal of Natural Fibers, 2022)
In this paper, an ultrasonic method has been developed to achieve a cleaner washing process for denim fabrics. At first, a comparison study was established between a conventional and an ultrasonic washing processes. Effects of reducing agent and sodium hydroxide concentrations, washing temperature and washing duration parameters were studied. Then, a factorial design was dressed to model the ultrasonic process. Regression equations for the color strength reduction Δ(K/S), lightness difference ΔL* and tensile force F(N) of washed denim fabrics were established. As results, efficience of ultrasonic process has been proven, fade appearance was obtained without degrading the textile material under several washing conditions. Hence, for a frequency of 25 kHz and a power of 300 W, and according to the degree of fade appearance of denim fabrics target, optimal ultrasonic washing conditions would be selected within these proposed intervals: a sodium hydroxide concentration lower than 15 g.L−1, a reducing agent concentration lower than 6 g.L−1, a washing temperature ranging from 50°C to 70°C and a washing duration ranging from 5 to 30 minutes. Finally, certain comfort properties of washed denim fabrics were evaluated. Both conventional and ultrasonic washing processes have been found to lead to similar thermal comfort properties.